HUBUNGAN KEKERABATAN 12 KULTIVAR BROKOLI (Brassica oleracea L.) BERDASARKAN KARAKTER ANATOMI STOMATA - Sri Risa Dewi, Ni Putu; Kriswiyanti, Eniek; Sugi Wahyuni, I Gusti Ayu (SIMBIOSIS; Vol 3 No 1 (2015), 2015)
This research aims to know the relationship of kinship in 12 cultivars Broccoli grown in Horticultural Nursery at Kembang Merta village Bedugul Bali. Broccoli leaf samples were taken from Horticultural Nursery at Kembang Merta village Bedugul Bali. The method used in this research is by utilizing fresh preparations of upside/downside leaf epidermal incision or Leaf Clearing method, the incision of the preparations and also the observations were carried out at the Laboratory of Plant Structure and Development Department of Biology, Faculty of Science and Mathematics, Udayana University. The results showed the existence of variations in epidermal cells, stomata structure, density and density of stomata on the 12 cultivars of Broccoli (Brassica oleracea L.) with the range index of similarity between 68,79% - 92,18% and formed the five groups that have different similarity indices in each group. Keywords: anatomy, broccoli (Brassica oleracea L.), similarity index of stomata